Bibliometric Analysis and Future Prospects of Sludge Treatment and Disposal Technologies in China - YUAN Xusheng; GAO Hong; HE Zishuai; ZHANG Zhishang; YAN Minjie (Renmin Zhujiang)
In order to understand the development status of sludge treatment anddisposal research in China in the past 30 years, and clarify the research hotspotsin this field, based on the Chinese core journals included in CNKI as the datasource, this paper retrieves 9318 related papers published from 1992 to 2019,draws the visual atlas by visual measurement software Citespace and bibliometrics,and obtains the cooperative knowledge map of domestic authors, the cooperativeknowledge map of domestic research institutions, the cluster analysis map ofhigh-frequency keywords, the frontier map of research time zone, and the stronghighlight word chart for sludge treatment and disposal field through Citespace.The results show that the number of annual publications in the field of sludgetreatment and disposal in China shows an overall trend of increase: Researchinstitutions are dominated by universities, and the cooperation among institutionsis relatively close, with initial model. The research direction in the field ofsludge treatment and disposal is gradually changing from environmental treatmentto sludge resource utilization. Carbon source, hydrolytic acidification, sludgeanaerobic digestion, high-throughput sequencing, microbial community structure,MBR (membrane bioreactor), sludge compost, etc. may become future researchhotspots.